The Psycho-Linguistic Analysis of the Process of Developing Speech Competence of the Students of Non-Philological Departments - Normatova, Nurjamol; Nazarov, Suyunbek (The Lingua Spectrum, 2026)
This comprehensive research article examines the psycho-linguistic foundations of speech competence development in university students from non-philological departments. Drawing upon contemporary research in psycholinguistics, cognitive psychology, and language pedagogy, this article synthesizes current understanding of the cognitive mechanisms, psychological processes, and pedagogical approaches that facilitate foreign language communicative competence in non-language majors. The integration of technology into foreign language instruction offers significant potential for enhancing speech competence development in non-philological students. The synthesis of contemporary research demonstrates that effective speech competence development requires instructional approaches that are simultaneously grounded in psycholinguistic theory, responsive to the unique constraints of non-philological contexts, and oriented toward the professional communication needs of students. Research examining the effectiveness of interactive online courses for speech competence development in non-language-major students has identified several key factors contributing to successful outcomes. The analysis reveals that speech competence development in this population is fundamentally shaped by the interplay of cognitive processes including memory, perception, attention, and thinking, alongside speech production mechanisms and language acquisition processes.